2018
DOI: 10.3390/su10061949
|View full text |Cite
|
Sign up to set email alerts
|

Measures and Steps for More Efficient Use of Buildings

Abstract: Abstract:As urbanization continues and more people move into cities and urban areas, pressure on available land for new constructions will continue to increase. This situation constitutes an incentive to review the need for interior space and uses of existing buildings. A great deal can be gained from using existing buildings more efficiently instead of constructing new ones: Reduced resource usage during construction (investments, natural resources, and energy), operation, and maintenance; more activity per s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…The four-step principle can be strongly supported by new measures (kWh/activity instead of kWh/m 2 ) and digitalization has a key role in creating opportunities for using space more efficiently and thus reduce demand. This has potentially large-scale effects on how cities and regions work and on total energy use in the building stock and for building new buildings [92]. Human-machine interaction must be considered as a form of social interaction and self-reflection.…”
Section: Commentmentioning
confidence: 99%
“…The four-step principle can be strongly supported by new measures (kWh/activity instead of kWh/m 2 ) and digitalization has a key role in creating opportunities for using space more efficiently and thus reduce demand. This has potentially large-scale effects on how cities and regions work and on total energy use in the building stock and for building new buildings [92]. Human-machine interaction must be considered as a form of social interaction and self-reflection.…”
Section: Commentmentioning
confidence: 99%
“…This paper explores two areas where a research need has been identified connected to space sharing. One aim is to improve the understanding of the processes involved in the implementation of space sharing and identifying aspects that deserve close attention when working with space sharing, as mentioned by Brinkø & Nielsen (2018) and Höjer & Mjörnell (2018). Another aim is to investigate the use of appropriate metrics for energy efficiency in shared spaces, as highlighted by Sekki, Airaksinen & Saari (2015).…”
Section: Aim and Research Questionsmentioning
confidence: 99%
“…Francart, Malmqvist & Hagbert (2018) highlight indoor space efficiency as a strategy to meet climate targets in the building sector, as it reduces the amount of new construction and operational energy demand. Similarly, Höjer & Mjörnell (2018) suggest a 'four-step principle' for a more efficient use of buildings. According to the principle, the first priority should be to adjust activities to require less space (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations